Penerapan Sanksi Disiplin terhadap Narapidana Yang Melakukan Pelanggaran Disiplin di Lembaga Pemasyarakatan Perempuan Kelas II B Jambi - Dedy Syaputra; Said Sahabuddin (Universitas Batanghari Jambi, 2023)
At present there have been violations committed by convicts in prisons, including the persecution of fellow criminals. Therefore, this research was conducted through empirical legal methods, which used a legal sociological approach, and there were three types of data sources, namely primary legal materials and secondary legal materials. The sampling technique was purposive sampling using data collection methods, namely interviews and documentary research to develop qualitative analysis. The matter of this research is the application of disciplinary sanctions against convicts who commit disciplinary violations based on Permenkumham Number 6 of 2013 in Class II B Jambi Women's Correctional Institutions is that there is no disciplinary action that will be taken against convicts of abuse cases in these prisons and the obstacles encountered in applying sanctions Discipline for convicts who commit disciplinary violations based on Permenkumham Number 6 of 2013 in the Jambi Class II B Women's Penitentiary is the lack of porcelain Class IIB Jambi Women's Prison, lack of support from inmates and inadequate infrastructure.